Chronic Type A Aortic Dissection Repair in a Double Lung Transplant Recipient - Kamat, Neeraj; Traify, Ragheb; Williams, Brian; Dimarakis, Ioannis (AORTA, 2021)
A 69-year-old man presented with a chronic Stanford Type A aortic dissection (CTAAD). The patient had undergone bilateral sequential lung transplantation 15 years prior for α-1-antitrypsin deficiency. We describe the management of CTAAD in the context of lung transplantation from the surgical and anesthetic perspectives.
Keywords: lung transplantation; chronic aortic dissection; Stanford Type A aortic dissection